A comparative study of the physical fitness levels of Indian and White pupils between the ages of 10 and 14 years - Kelder, R. J.(Reindert Jan) (Stellenbosch : Stellenbosch University, 2012)
Photo-copy of original thesis, University of Stellenbosch, 1984.